РОЗВИТОК ПРИНЦИПІВ ПОБУДОВИ АПАРАТУРИ ДЛЯ РЕАЛІЗАЦІЇ МЕТОДУ АМПЕРОСТАТИЧНОЇ КУЛОНОМЕТРІЇ - Ламеко, О.Л.; Петренко, А.В.; Мельник, В.Г.; Василенко, О.Д.; Мельников, О.О. (Інститут електродинаміки НАН України, Київ, 2024)
Тhe methods of amperostatic coulometry and the design of existing equipment for their application are analyzed. A new approach to the design of a coulometric system for the National Amount of Substance Electrochemical Standard is proposed. It consists in combining the means for performing the main operations of the primary amperostatic coulometry method in a single hardware and software unit that performs titration and automated control of this process, as well as receiving and processing the measuring signals required for this. The structure and functional diagram of the measuring unit of a precision automatic coulometry titrator using the latest element base are developed. The appearance and brief description of the created compact measuring system are given. The proposed algorithm for inversion of the measured voltage is described, which made it possible to significantly improve the accuracy of titration current measurement. A new version of median filtration of the measuring signal is presented, which made it possible to increase the accuracy of recording changes in the solution potential and determining the moment of end of the electrochemical reaction. The effectiveness of the developed technical solutions is confirmed by the results of international comparisons, to which references are provided. References 18, figures 4.